PENERAPAN MEDIA PEMBELAJARAN VIDEO ANIMASI PADA MATERI PEWARISAN SIFAT TERHADAP HASIL BELAJAR SISWA KELAS IX DI SMP NEGERI 4 GLENMORE - Ningsih, Fitria; Danuji, Sarwo; Putri, Hanif Rafika (Universitas Khairun, 2025)
This study aims to improve student learning outcomes through the use of animated video learning media in the Natural Sciences subject for Grade IX students at SMP Negeri 4 Glenmore. The background of this research is the low student learning outcomes and the limited availability of learning media at school, which affects students' learning interest. This research employs Classroom Action Research (CAR), which is carried out in two cycles and consists of four stages: planning, implementation, observation, and reflection. The subjects of the study were 28 Grade IX students of SMP Negeri 4 Glenmore. Data collection techniques were conducted through learning outcome tests, including pre-tests and post-tests. The results of the study show that the use of animated video media can improve student learning outcomes in each cycle, with a pre-cycle average score of 70.53 and a mastery percentage of 43%, which increased in the first cycle to an average of 81.60 and a mastery percentage of 68%, and further increased in the second cycle to an average of 91.25 and a mastery percentage of 96%. Thus, animated video learning media are effective in improving student learning outcomes.